2012
DOI: 10.1155/2012/129486
|View full text |Cite
|
Sign up to set email alerts
|

Th2 Regulation of Viral Myocarditis in Mice: Different Roles for TLR3 versus TRIF in Progression to Chronic Disease

Abstract: Viral infections are able to induce autoimmune inflammation in the heart. Here, we investigated the role of virus-activated Toll-like receptor (TLR)3 and its adaptor TRIF on the development of autoimmune coxsackievirus B3 (CVB3) myocarditis in mice. Although TLR3- or TRIF-deficient mice developed similarly worse acute CVB3 myocarditis and viral replication compared to control mice, disease was significantly worse in TRIF compared to TLR3-deficient mice. Interestingly, TLR3-deficient mice developed an interleuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(106 citation statements)
references
References 34 publications
3
99
2
2
Order By: Relevance
“…Hearts were fixed in 10% buffered formalin and stained with hematoxylin and eosin to assess inflammatory cells or Masson's trichrome to detect collagen deposition. Myocarditis was assessed as the percentage of the heart section (i.e., ventricles) with hematoxylin staining, necrosis, and/or fibrosis compared with the overall size of the heart section at low power (ϫ25 magnification) using a microscope eyepiece grid, as has been done previously (1,2,11,18). Sections were scored by at least two individuals blinded to the treatment group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hearts were fixed in 10% buffered formalin and stained with hematoxylin and eosin to assess inflammatory cells or Masson's trichrome to detect collagen deposition. Myocarditis was assessed as the percentage of the heart section (i.e., ventricles) with hematoxylin staining, necrosis, and/or fibrosis compared with the overall size of the heart section at low power (ϫ25 magnification) using a microscope eyepiece grid, as has been done previously (1,2,11,18). Sections were scored by at least two individuals blinded to the treatment group.…”
Section: Methodsmentioning
confidence: 99%
“…TLR3 polymorphisms in myocarditis patients were recently found to be associated with an increased susceptibility to enteroviral myocarditis and DCM (30), suggesting that TLR3 may be important in protecting against the progression from myocarditis to iDCM. Recently, we showed that TLR3-deficient mice develop a T helper (Th)2-skewed immune response during acute CVB3 myocarditis and that an IL-4-driven Th2 response has less severe consequences than an IL-33-driven Th2 response on cardiac function (1,2). In this study, we further examined the mechanisms involved in protection mediated by TLR3 in the progression from myocarditis to iDCM.…”
mentioning
confidence: 97%
“…47 Mouse studies have shown that a deficiency of either TLR3 or its adaptor, TRIF, is associated with an increase in levels of virus and mortality after CVB3 or CVB4 infection. [48][49][50] Interestingly, type I IFNs (IFN-a and IFN-b), but not type II IFN (IFN-g), are required for the innate immune response to CVB3. 51 IFN-a and IFN-b are expressed at low levels by various cells but are induced in virally infected cells, such as CFs and cardiomyocytes in the heart.…”
Section: Par1 Modulation Of Tlr3 and Tlr4 Signaling In Cfsmentioning
confidence: 99%
“…Although the virus is directly responsible for some organ injury, the majority of the injury is caused by the host inflammatory response to the virus (46). TLR3 or TRIF deficiency is associated with increased viral titers and a higher mortality after infection with CVB3 or CVB4 (47)(48)(49). Type I IFN signaling, but not type II IFN signaling, is required for an innate immune response to CVB3 infection (50).…”
Section: Introductionmentioning
confidence: 99%